Asymmetric transfer hydrogenation of aryl ketoesters with a chiral double-chain surfactant-type catalyst in water. Issue 22 (30th October 2017) - Li, Jiahong; Lin, Zechao; Huang, Qingfei; Wang, Qiwei; Tang, Lei; Zhu, Jin; Deng, Jingen
Abstract : A chiral double-chain surfactant-type ligand was designed and synthesized. The rhodium catalyst formed from the ligand can self-assemble into chiral vesicular aggregates in water, which was applied to ATH of broad range of aromatic ketoesters in neat water. Abstract : A chiral double-chain surfactant-type ligand was designed and synthesized. The rhodium catalyst formed from the ligand can self-assemble into chiral vesicular aggregates in water, which was applied to the ATH of a broad range of aromatic ketoesters in neat water and gave up to 99% yield and 99% ee. In addition, this double-chain surfactant-type catalyst could also be applied to the dynamic kinetic resolution (DKR) of bicyclic β-ketoesters in water.